Harmony Between Heritage and Sundanese Culture: An Evaluation of Tourists’ Perceptions of Braga’s Small and Medium-Sized Enterprises And Their Contribution to Gross Domestic Product - Dinda Tifani; Indriyani Agustina; Ilham Wiradinata; Muhamad Aditya . A; Stefani Oktavia; Rizky Nugraha; Alfachru Roziq (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines tourists’ perceptions of small and medium sized enterprises operating within the heritage tourism environment of Braga, Bandung, and investigates their perceived contribution to local economic development. The research employs an empirical qualitative approach using observations, semi structured interviews, and documentary analysis involving tourists and enterprise actors. Data were analyzed through thematic coding, categorization, and interpretative analysis to identify relationships among tourism experience, cultural values, enterprise performance, and economic perceptions. The findings reveal that tourists positively evaluate local enterprises through the quality of products, cultural authenticity, and destination experiences associated with the heritage character of Braga. The Sundanese philosophy of Someah Hade Ka Semah emerges as a significant cultural asset that strengthens hospitality, responsiveness, courtesy, and respectful communication, thereby enhancing tourist satisfaction and destination attachment. Positive visitor experiences are further reflected in spending behavior, revisit intentions, and destination recommendations that reinforce enterprise competitiveness and local economic activity. The study concludes that the interaction between heritage assets, cultural values, and entrepreneurial practices creates a sustainable tourism environment that generates perceived economic contributions and supports broader regional development objectives.